Miniaturized tri-band filtering-response power divider with short- and open-stub-loaded resonators. Issue 8 (14th August 2017) - He, Zongrui; Song, Kaijun; Zeng, Bo; Zhu, Yu; Fan, Yong
Abstract : A miniaturized tri-passband power divider integrating a power divider with two tri-band bandpass filters is presented. The short- and open-stub-loaded resonators are used in this presented power divider to implement the bandpass-filtering response. Then, the presented power divider has not only the power-dividing/combining function, but also the tri-passband filtering response. When the central frequency of the second passband is fixed, the other two passband central frequencies of the tri-band power divider can be flexibly controlled by changing the lengths of the stubs. The even- and odd-mode equivalent circuits of the proposed tri-band power divider are analyzed, and the design equations are derived, which can be used to guide the design of the presented miniaturized tri-passband power divider. The measured results agree well with the simulated ones.